Economics of Good or Bad? Contemporary Paradoxes in Economy and Economics - Michalski, Michał. A (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
Economics plays important role in contemporary societies and shapes our thinking about fundamental aspects of everyday life. If that is the case, it is necessary to analyse economic theories from the axiological point of view. It does not only has theoretical importance but practical as well when we consider recent financial and economic crisis when economists were asked to explain how and why was it possible for the 21st century economy and economics to fail so seriously. The article reflects on these issues and presents examples of paradoxes in contemporary economics and economy which show that critical evaluation of what our societies consider true and right in terms of material reproduction and social well-being is necessary. It also asks about ‘good economics’ which will not only adequately describe and interprete real economic processes but also serve as the useful and effective tool for accomplishing economic and social – morally acceptable – development. In order to do this the article analyses and verifies foundations and assumptions of current economic theory. It engages the contribution of personalistic perspective and authors like John D. Mueller, Tomáš Sedláček, Joseph E. Stiglitz, Amartya Sen, Gary S. Becker, Chantal Delsol and Grzegorz W. Kołodko who offer interesting arguments in the discussion about the proper shape of economics which will facilitate economic and human development as well.